2020
DOI: 10.1101/2020.07.25.20161968
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing the quality of nontraditional N95 filtering face-piece respirators available during the COVID-19 pandemic

Abstract: Background: During the current COVID-19 pandemic, supply chains for Personal Protective Equipment (PPE) have been severely disrupted and many products, particularly surgical N95 filtering facepiece respirators (FFRs; "masks") are in short supply. As a consequence, an Emergency Use Authorization (EUA) from the FDA has allowed importation of N95-type masks manufactured to international standards; these include KN95 masks from China and FFP2 masks from the European Union. Methods: We conducted a survey of mask i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…Some KN95 masks, although filtration integrity was of adequate standard, therefore still failed on facial seal and inward leakage of particles. Plana et al [8] (non-peer reviewed data in preprint format) also found that several KN95 masks failed to meet mask filter integrity thresholds. Their article highlighted that a high proportion of KN95 masks may be counterfeit.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some KN95 masks, although filtration integrity was of adequate standard, therefore still failed on facial seal and inward leakage of particles. Plana et al [8] (non-peer reviewed data in preprint format) also found that several KN95 masks failed to meet mask filter integrity thresholds. Their article highlighted that a high proportion of KN95 masks may be counterfeit.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly available substitute for the N95 mask has been the KN95 mask, which is mainly manufactured in China to the GB2626-2006 standard, and which is considered equivalent to the N95 by the US Food And Drug Administration (FDA) following Emergency Use Authorisation based on testing of filtration efficacy of the mask material. [8] The manufacture of N95-like masks remains highly regulated in order to ensure that they filter out at least 95% of penetrating aerosol particles ≄0.3 ”m in diameter, fit tightly to maximise the passage of inhaled air through the filter fabric of the mask, and have low inhalational resistance to minimise breathing difficulty. There has been a growing concern about the quality of the circulating supplies of N95-like masks in many parts of the world, including the circulation of counterfeit masks.…”
Section: Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…To avoid forgetting the lessons of COVID-19 pandemic, it is essential that innovative designs and approaches be further developed, tested, and integrated into normal regulatory chains so they are ready for future emergencies. Changes in regulatory policies would also enable a middle ground, balancing the rigidity of the pre-crisis approach with the free-for-all and counterfeiting 80 unintentionally enabled by EUAs. We envision the development of open-source repositories, such as NIH 3D Print Exchange, to facilitate independent testing of products to meet key NIOSH, FDA and other requirements for functionality and safety.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%